Thermal and ballistic characterization of epoxy matrix composites reinforced with babassu (Attalea speciosa) fiber: An experimental investigation - Lucas Moura Montenegro Reis; Pedro Henrique Poubel Mendonça da Silveira; Yago Soares Chaves; Rafael Travincas Pinto; Lucas de Mendonça Neuba; Sergio Neves Monteiro; Lucio Fabio Cassiano Nascimento (Journal of Materials Research and Technology)
This work focused on developing lightweight and cost-effective ballistic shields using epoxy matrix composites reinforced with short babassu fibers. Composites containing 10, 20, and 30 vol% fiber content were produced via compression molding and assessed for their chemical composition, thermal properties, and ballistic performance. Characterization techniques included Fourier transform infrared spectroscopy (FTIR), which revealed interfacial bonding between fibers and the matrix, indicated by the intensification of the band at 1608 cm⁻1. Thermogravimetric analysis (TGA) demonstrated a 6% reduction in thermal stability for composites with 10 vol% fibers, due to premature fiber degradation, with less pronounced effects at higher fiber fractions. Ballistic tests showed a decrease in energy absorption from 230 J in composites with 10 vol% fibers to 212 J for those with 30 vol%, attributed to a shift in failure mechanisms from brittle fractures in the matrix to fiber debonding and rupture. However, the 30 vol% fiber composites displayed greater damage tolerance and structural integrity, remaining intact after five successive impacts. A cost analysis revealed that these composites are 98% cheaper than A500 steel and 82% cheaper than ultra-high molecular weight polyethylene, both widely used in armor. These results highlight the potential of babassu fibers as an economical and sustainable reinforcement for polymer composites, reducing production costs while maintaining satisfactory performance, and offering a viable solution for manufacturing lighter, affordable ballistic shields.